2008
DOI: 10.1590/s1517-86922008000600014
|View full text |Cite
|
Sign up to set email alerts
|

Treino de corrida não interfere no desempenho de força de membros superiores

Abstract: RESUMOObjetivo: O presente estudo avaliou o efeito do exercício de endurance (corrida) sobre o subseqüente desempenho de força de músculos dos membros superiores e do tronco. Metodologia: A amostra foi composta por 13 universitárias, saudáveis e fisicamente ativas. A primeira fase do experimento consistiu na realização de um teste de corrida, simulando uma sessão de treino, com duração de 45 minutos a 70% da FC MAX . Imediatamente após a corrida, foram aplicados testes de força (dinamometria -preensão palmar, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
1
5
1
4
Order By: Relevance
“…Moreover, the reduction in force was not observed after the endurance exercise under temperate conditions. Thus, the results of this study contradict the position adopted by Raddi et al (2008), 26 who, after not observing the influence of a running protocol (45 min at 70% VO 2max ) on force production, concluded that interference observed in the concurrent exercise is dependent on prior recruitment of the same muscle group.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, the reduction in force was not observed after the endurance exercise under temperate conditions. Thus, the results of this study contradict the position adopted by Raddi et al (2008), 26 who, after not observing the influence of a running protocol (45 min at 70% VO 2max ) on force production, concluded that interference observed in the concurrent exercise is dependent on prior recruitment of the same muscle group.…”
Section: Discussioncontrasting
confidence: 99%
“…correlation between these two variables, which corroborates the existence of an association between a rise in T CORE and a reduction in neuromuscular function, 5 regardless of changes in muscle or skin temperature. 6,7 Thus, it is likely that in the study of Raddi et al (2008), 26 the increase in T CORE was not great enough to reduce force -as is supported by our results obtained in the temperate environment. On the other hand, the study by Nybo and Nielsen (2001) 5 reported an 18% force reduction in post-endurance exercise performed in a temperate environment; however, the 1.1°C temperature increase registered by the latter authors (from 36.9 to 38.0°C) was higher than that observed in the present study (0.46°C) and reinforces the relationship between the magnitude of the T CORE rise and the reduction in force.…”
Section: Discussionsupporting
confidence: 66%
“…Foram encontrados 17 artigos sendo que 9 estudos enfocaram em provas de meio fundo e fundo [16][17][18][19][20][21][22][23][24] , 3 em corredores de rua recreacionais [25][26][27] , 1 de maratona 28 , 3 de provas de velocidade [29][30][31] e 1 em atletas Paralímpicos 32 . Todos os estudos selecionados apresentaram delineamento transversal.…”
Section: Fisiologia Do Exercíciounclassified
“…Raddi et al (18) demonstraram que a atividade de endurance não promoveu alteração na concentração plasmática de glicose, durante a aplicação de protocolo de força após treinamento aeróbico. Para os autores, a manutenção da glicemia associada à ausência de interferência sobre o desempenho dos testes de força reforça, mais ainda, a hipótese de que o efeito adverso do treinamento concorrente é, provavelmente, causado por alterações periféricas musculoespecíficas.…”
Section: Discussionunclassified